2010
DOI: 10.1007/s10735-010-9257-7
|View full text |Cite
|
Sign up to set email alerts
|

Type II and VI collagen in nasal and articular cartilage and the effect of IL-1α on the distribution of these collagens

Abstract: The distribution of type II and VI collagen was immunocytochemically investigated in bovine articular and nasal cartilage. Cartilage explants were used either fresh or cultured for up to 4 weeks with or without interleukin 1α (IL-1α). Sections of the explants were incubated with antibodies for both types of collagen. Microscopic analyses revealed that type II collagen was preferentially localized in the interchondron matrix whereas type VI collagen was primarily found in the direct vicinity of the chondrocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…With regard to HA, no discernible change in PCM morphology or PG content was observed following up to 10 hours of digestion with ovine testicular hyaluronidase (Poole et al, 1985), which has demonstrated activity toward both HA and chondroitin derivatives (Menzel and Farr, 1998). Similarly, other studies have shown little effect of Hyal or interleukin 1a treatment on collagen VI distribution of PCM architecture in articular cartilage (Jansen et al, 2010). However, collagenase digestion of articular cartilage completely degrades the ECM but leaves the chondron (chondrocyte and its PCM) intact, although the mechanical properties of the PCM are greatly reduced in this case (Guilak et al, 1999) as compared to the in situ properties (Darling et al, 2010) and those of mechanically isolated chondrons (Guilak et al, 2005).…”
Section: Discussionmentioning
confidence: 77%
“…With regard to HA, no discernible change in PCM morphology or PG content was observed following up to 10 hours of digestion with ovine testicular hyaluronidase (Poole et al, 1985), which has demonstrated activity toward both HA and chondroitin derivatives (Menzel and Farr, 1998). Similarly, other studies have shown little effect of Hyal or interleukin 1a treatment on collagen VI distribution of PCM architecture in articular cartilage (Jansen et al, 2010). However, collagenase digestion of articular cartilage completely degrades the ECM but leaves the chondron (chondrocyte and its PCM) intact, although the mechanical properties of the PCM are greatly reduced in this case (Guilak et al, 1999) as compared to the in situ properties (Darling et al, 2010) and those of mechanically isolated chondrons (Guilak et al, 2005).…”
Section: Discussionmentioning
confidence: 77%
“…[21,22] More recently, Pitter and co-workers described the hydrosilylation of CO 2 catalyzed by ruthenium-acetonitrile complexes, yielding formoxysilanes. [23][24][25] Matsuo and Kawaguchi reported the homogeneous reduction of CO 2 with hydrosilanes catalyzed by zirconium-borane complexes, yielding methane. [26] The practicality of applications of these different systems was limited by their sensitivity to air and moisture, as well as the low activities of the organometallic catalysts.…”
mentioning
confidence: 99%
“…In contrast, a zirconium catalyst [26] was reported to have TON and TOF values of only 92 and 0.54 h À1 , respectively, and ruthenium catalysts achieved values of 78-400 and 2.8-17 h À1 , respectively, at elevated temperatures and high CO 2 pressures (40 atm). [23][24][25] The reaction with the [Ir(CN)(CO)(dppe)] catalyst (dppe = (1,2-bis(diphenylphosphanyl)ethane)) produced a similar SiOMe end product with very low efficiency (TON = 2.28, TOF = 0.007 h À1 ). [22] These results demonstrate that nucleophilic NHC acts as an excellent CO 2 activator.…”
mentioning
confidence: 99%
“…CD44 is a glycoprotein and able to bind to matrix molecules such as hyaluronic acid and laminin in the extracellular matrix . Type II collagen is the main component of the hyaline matrix of hyaline cartilage . In our work, chondrocytes were isolated from the acetabular cartilage complex and identified by immunofluorescence with CD44 antibody and collagen II antibody (Figure S2A) .…”
Section: Resultsmentioning
confidence: 93%
“…21,22 Type II collagen is the main component of the hyaline matrix of hyaline cartilage. 23,24 In our work, chondrocytes were isolated from the acetabular cartilage complex and identified by immunofluorescence with CD44 antibody and collagen II antibody ( Figure S2A). 25 To explore the effect of WISP-2 on chondrocyte apoptosis, the WISP-2 was overexpressed and knocked down in chondrocytes by 72 hours lentivirus infection.…”
Section: Wisp-2 Overexpression Induces Chondrocyte Apoptosismentioning
confidence: 99%